2018
DOI: 10.1111/gbb.12458
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12 deficiency in mouse impairs noradrenergic system in brain, and alters anxiety‐like neurobehavior and memory

Abstract: Purinergic receptor P2Y (P2Y ), a G protein-coupled purinergic receptor, is widely distributed in nervous system and involved in the progression of neurological diseases such as multiple sclerosis and neuropathic pain. The central noradrenergic system actively participates in a number of neurophysiological processes. Nevertheless, whether there is any direct relevance between P2Y and noradrenergic signal transduction remains unknown. In the present study, we tested the hypothesis that lack of P2Y impaired nora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…In these experiments, we showed that unlike ocular dominance plasticity in the adolescent visual cortex, P2Y12 is not required for synaptic remodeling in the early development of the LGN, a process that is known to depend on microglia, nor is it required for microglial distribution within developing barrels in the somatosensory cortex. However, in line with previous investigations [25,26], the loss of P2Y12 results in altered behavior in the adult mouse, including increased anxiety, decreased social interactions, and more heterogeneous effects on learning. This suggests that loss of P2Y12 alters neural circuits and impacts adult brain function.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In these experiments, we showed that unlike ocular dominance plasticity in the adolescent visual cortex, P2Y12 is not required for synaptic remodeling in the early development of the LGN, a process that is known to depend on microglia, nor is it required for microglial distribution within developing barrels in the somatosensory cortex. However, in line with previous investigations [25,26], the loss of P2Y12 results in altered behavior in the adult mouse, including increased anxiety, decreased social interactions, and more heterogeneous effects on learning. This suggests that loss of P2Y12 alters neural circuits and impacts adult brain function.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have reported changes in animal behavior after the disruption of microglial pathways that contribute to synapse remodeling [27][28][29]. Recently, a pair of studies examined the role of P2Y12 in fear acquisition and anxiety-like behaviors, finding that P2Y12 is required for innate fear learning and its loss increases anxiety-like behaviors [25,26]. In line with these results, we found enhanced anxiety-like behaviors in P2Y12 −/− mice as measured by FST, underscoring the function of P2Y12 in mediating anxiety responses.…”
Section: P2y12 and Behaviormentioning
confidence: 99%
“…The OFT was administrated as described previously [46]. In brief, the mice were individually placed into the center of an open box apparatus (50 cm × 50 cm × 40 cm) with a black floor.…”
Section: Open Field Testmentioning
confidence: 99%
“…It was made of opaque plexiglass with manually operated doors lead from the hub of the central maze to each arm. RAMT was conducted in accordance with the procedure described previously, with minor modi cation [27]. As shown in Fig.…”
Section: Behavioral Testsmentioning
confidence: 99%